Perencanaan Rute Aman Selamat Sekolah (RASS) di Kawasan Pendidikan Kota Surakarta : Pembebanan Rute dan Pemenuhan Fasilitasnya - Pambudi, Muhammad Aryant Setya; Aprianto, Rizal; Hadi, Suprapto (Jurnal Aplikasi Teknik Sipil, 2024)
Banjarsari Sub-district has the highest density in Surakarta City causing traffic to be crowded and less friendly for students travelling. The need to improve student safety by providing safe road equipment facilities is the purpose of applying the RASS concept. The OD Matrix method was used to see the distribution of students divided into 22 zones based on administrative boundaries, PKJI 2023 and EAN were used to analyse the loading of student travel routes, and to analyse the fulfilment of pedestrian, cycling and public transport facilities, relevant guidelines were used. RASS conceptualised travel routes were created for the demand of the zones with the largest generation, which came from zone 20, zone 4, and zone 21. The recommended pedestrian facilities are sidewalks on each pedestrian route and zebra crossing facilities. The addition of special bicycle lanes and lanes is recommended on 3 routes consisting of 9 road sections.